2005
DOI: 10.1111/j.1467-842x.2005.tb00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Young people's use of condoms and their perceived vulnerability to sexually transmitted infections

Abstract: Objective: Although sexually transmitted infections (STIs) are most prevalent among young people, they do not use condoms consistently to prevent infection. This study examined young people's perceptions of vulnerability to STIs and pregnancy. Method: A cross‐sectional survey on sexual behaviour was carried out on a stratified random sample of school‐going Year 12 and Year 13 young people aged 16–18 years in Christchurch, New Zealand. Results: 1,136 students participated in the study, half of whom were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
4
27
1
Order By: Relevance
“…Abel and Brunton in a study of year 12 and year 13 secondary schools students (mean age = 16.6 years) in Christchurch, New Zealand, found 49% of students had engaged in sexual intercourse. 8 The rates of sexual intercourse found in the Australian data were higher than those found by Henderson et al in Scotland,5 however this difference is likely attributable in some part to the lower mean age of the Scottish sample (mean = 14.2 years).…”
Section: Discussioncontrasting
confidence: 49%
“…Abel and Brunton in a study of year 12 and year 13 secondary schools students (mean age = 16.6 years) in Christchurch, New Zealand, found 49% of students had engaged in sexual intercourse. 8 The rates of sexual intercourse found in the Australian data were higher than those found by Henderson et al in Scotland,5 however this difference is likely attributable in some part to the lower mean age of the Scottish sample (mean = 14.2 years).…”
Section: Discussioncontrasting
confidence: 49%
“…11 In New Zealand, 77% of 538 male and female high school students aged 16 -18 in Christchurch felt that it was unlikely that they would get a sexually transmitted infection. 12 In Nepal, 77% of 348 sexually active male and female migrant factory workers aged 14-19 felt that they were not at all at risk of contracting any STI or HIV/AIDS. 13 In our study of 3336 male and female high school students who were participating in a school-based screening for chlamydia and gonorrhoea, 64% estimated that their chances of getting infected with an STI were not pretty high or very high.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, studies have also shown that people who are in permanent relationships do not practice safer sex (Abel and Brunton 2004;Misovich et al 1997), as illustrated in Croatian 18-24 year-olds, where 17% of the females and 31% of the males reported having had concurrent relationships (Š tulhofer et al 2009), thus increasing the risk of STI transmission. That extradyadic activity represents a risk of STI transmission has also been documented in Norway, where people tend not to use condoms during sex (Traeen et al 2007).…”
Section: Risk Assessmentmentioning
confidence: 93%